Inside the black box: The accuracy of alternative stress test models - Paul H. Kupiec (American Enterprise Institute (AEI), 2018)
Regulatory forecasts of bank performance over hypothetical multiyear stress scenarios are used to set financial institution minimum regulatory capital requirements in multiple jurisdictions, yet little is known about the accuracy of these supervisory stress test models.
Keywords: A; 330; Financial institutions; banks; stress tests